2020
DOI: 10.3390/cells9030596
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Aspects of Metabolic Plasticity in Human Cholangiocarcinoma: An Overview of Current Perspectives

Abstract: Cholangiocarcinoma (CCA) is a deadly tumor without an effective therapy. Unique metabolic and bioenergetics features are important hallmarks of tumor cells. Metabolic plasticity allows cancer cells to survive in poor nutrient environments and maximize cell growth by sustaining survival, proliferation, and metastasis. In recent years, an increasing number of studies have shown that specific signaling networks contribute to malignant tumor onset by reprogramming metabolic traits. Several evidences demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 206 publications
(285 reference statements)
1
13
0
Order By: Relevance
“…67 Likewise, CCA also demonstrated reprogrammed metabolism, including classical Warburg effects with glucose dependency, increase in oxidative phosphorylation capacity, enhanced lipid uptake and oxidation with possible dependence on sphingosine, and upregulation of glutaminolysis. 91 Historically, this is thought to be dictated by cell-intrinsic factors, such as genomic alteration and aberrate cell signaling. However, emerging studies have identified the importance of TME, parental tissue architecture, and systemic metabolism as essential contributors to tumor metabolism.…”
Section: Reprogrammed Tumor Metabolismmentioning
confidence: 99%
“…67 Likewise, CCA also demonstrated reprogrammed metabolism, including classical Warburg effects with glucose dependency, increase in oxidative phosphorylation capacity, enhanced lipid uptake and oxidation with possible dependence on sphingosine, and upregulation of glutaminolysis. 91 Historically, this is thought to be dictated by cell-intrinsic factors, such as genomic alteration and aberrate cell signaling. However, emerging studies have identified the importance of TME, parental tissue architecture, and systemic metabolism as essential contributors to tumor metabolism.…”
Section: Reprogrammed Tumor Metabolismmentioning
confidence: 99%
“…IDH mutation is the most important genetic change in glioma. The mutation is located at the isocitric acid binding site (Arg/R132 of IDH1 and R172 of IDH2) of a single amino acid ( 3 , 4 ). IDH1/2 mutations are common in World Health Organization (WHO) grade II and III gliomas and secondary glioblastoma (GBM; 70–80%), while primary GBM (WHO grade IV) IDH1/2 mutations are rare (<5%) ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 522 genes from turquoise module signi cantly correlated with risk score model were mainly enriched in metabolic-related biological pathways and PPAR signaling pathway. These pathways are well documented as participating in the carcinogenesis and progression of CCA [36]. Various studies based on multiple CCA independent cohorts [37][38][39] also detected that metabolic-related biological processes including small molecule and lipid metabolic processes relate to energy metabolism were pivotal for CCA development.…”
Section: Discussionmentioning
confidence: 93%